Peran Kampus Mengajar dalam Meningkatkan Literasi, Numerasi dan Adaptasi Teknologi Peserta Didik Sekolah Dasar di Sumatera Barat - Atri Waldi; Nana Meisah Putri; Indra Indra; Viero Ridalfich; Dina Mulyani; Enjel Mardianti (Journal of Civic Education, 2022)
This study aims to determine the role of the Kampus Mengajar in improving literacy, numeracy and technological adaptation of elementary school students in West Sumatra in order to improve the quality of education. This type of research uses a descriptive qualitative approach. This research was conducted for six months. The location of this study was carried out in three elementary schools in West Sumatra, namely SD Negeri 18 Anduring Padang, SD-IT Ar-Rahman Palangki, Sijunjung Regency and SD-IT Medina Lengayang Pesisir Selatan. Procedures, techniques and instruments of data collection using observation, interviews and documentation. So it can be concluded that the Kampus Mengajar in improving literacy, numeracy and technological adaptation has an important and successful role in running its program which is assisted by students and the support of the school and students.